Levels of Faecal Indicator Bacteria and Biofilm-Producing Escherichia Coli in Vembanad Lake, Kerala, India - Krishna Suresh; Visnuvinayagam, Sivam; Murugadas V.; V., Radhakrishnan Nair; G. K., Sivaraman; Toms C. Joseph (Fishery Technology, 2023)
Most of earlier investigations on pollution monitoring of bacteria have relied on the levels of E. coli in the aquatic environment with limited investigation on their biofilm producing ability. The capacity of a bacteria to produce biofilm is closely related to its pathogenicity. Vembanad Lake in Kerala is the longest lake in India, with 1.6 million people living on its shores and relying on it for their livelihood either directly or indirectly. The study was conducted to assess the level of biofilm-producing E. coli in Vembanad Lake. A Niskin water sampler was used to collect samples after mapping 34 locations and were used as sampling points. These location points covered the entire stretch of Vembanad Lake; Ernakulam, Kottayam, and Alappuzha regions. Faecal coliform (FC), E. coli and Faecal Streptococci (FS) in the water samples were enumerated using the 5-tube MPN method. The samples yielded 102 E. coli isolates, which were confirmed by polymerase chain reaction. All the isolates were checked for their biofilm formation ability. The study revealed that the Ernakulam region had the highest number of FC, FS and E. coli among the three regions. Among the E. coli isolates, 68, 14, 12 and 3 were weak, moderate, strong and very strong biofilm producers, respectively. It can be inferred that high prevalence of biofilm producing E. coli in Vembanad Lake indicate a potential hazard. It is recommended that the biofilm-forming capacity of E. coli be assessed along with routine monitoring since this ability of bacteria is associated with bacterial survival and invasiveness.